Farm Business Surveys as Sources of Data on Agricultural Income - Black, John D. (The Review of Economics and Statistics, 1928)
SINCE the first business survey was made in Tompkins County, New York, in I907 by Cornell University, well over eighty thousand business records have been taken in a total of something like 550 different areas in 45 different states in the United States. Mr. H. W. Hawthorne of the United States Bureau of Agricultural Economics assembled the principal facts for 7 I,55 I of these records in Table 652 (pp. I 285-I3II) in the I925 Yearbook of the United States Department of Agriculture. Since then, he has secured reports of about five thousand more records taken in fifty additional areas, and all the I927 reports are not yet in. It usually takes a year or more to work up the data of such surveys. In addition, there have been several thousands of other records taken in which data have been obtained with a somewhat different use in mind; for example, the progress records taken of settlers in cut-over or reclaimed areas, the progress records of groups of Southern farmers, the records of family living in which is obtained as a check against expenditures. Each of the business records contains an opening and closing inventory and a record of the receipts and expenditures of the year. From these are computed a farm income figure, and a labor income figure, the latter being the estimate resulting from an attempt to determine the return to the proprietor after a reasonable allowance for interest on investment has been deducted. No other industry has available such a large supply of data collected by educational and governmental agencies with avowedly scientific intent. It is not strange, therefore, that most of those interested in estimating the of agriculture have turned to these survey reports as an important source of data. Data from these surveys figured in the findings of the Commission of Agricultural Inquiry,' in the estimates of incomes by the National Bureau of Economic Research,2 and indirectly in the reports of the National Industrial Conference Board and the Business Men's Commission. Workers in the general field of economics are constantly drawing upon these data of income. It is therefore highly desirable that we have a clear idea of their meaning and applicability.